Impact of sodium chloride on shear behavior of saline soil with high sulfate during cooling. (December 2022) - Zhang, Yu; Ma, Ying; Tian, Runze; Zhang, Hui; Zhang, Yan; Jia, Fan
Abstract: Saline soils are widespread in the northwest and northeast inland regions of China, among which chloride saline soils and sulfate saline soils are prevalent in the northwest region, subgrade engineering activities have increased. To find sodium chloride (NaCl) impact on shear behavior of saline soil subgrade fillers in cold season, a fine-grained saline soil was sampled along highway from Qarhan to Golmud on the Qinghai-Tibet plateau and were added NaCl varying from 2% to 8% to conduct laboratory direct shear testing in a cool environment. The tests of volumetric change and direct shear were performed at set key temperatures (20 °C, −10 °C, and −20 °C) to obtain the NaCl impact on shear behavior of saline soil with high sulfate during cooling. The test results demonstrate the following properties: (1) there is a critical value on the proportion of NaCl content ranging from 4% to 6% for shear behaviors of saline soil; (2) NaCl can effectively inhibit volumetric expansion when added NaCl vary from 0% to 4%, but volumetric expansion can't be suppressed at low temperature when NaCl content was added more than 6%; (3) the shear stress-strain relationships of saline soils with NaCl content of 2%–8% show strain softening behavior at set key temperatures (20 °C, −10 °C, and −20 °C); (4) during the cooling process, the cohesion of saline soil with different NaCl content increases in varying degrees, and when the sodium chloride content is greater than 4%, the increase of cohesion is more obvious. These conclusions show that the improvement of soil shear strength parameters during cooling are conducive to highway engineering, but NaCl content also has an adverse direct impact on the saline soil engineering, which is related to temperature, initial salt content, water content and different proportions of sulfate and chloride. Highlights: There is a critical value of NaCl content on the mechanical properties of saline soil. When adding NaCl less than 4%, the volume swelling of saline soil can be inhibition. The addition of NaCl is beneficial to highway engineering in saline soil.